Conceptualisation and Contextualisation of Mixed-Methods Research: A Review - Aramide, Kolawole Akinjide; Jacob, Udeme Samuel; Pillay, Jace (Research in Social Sciences and Technology, 2023)
The purpose of this study was to investigate the conceptualisation and contextualisation of mixed-methods research within the research methodology paradigm to ascertain the categorisation of mixed methods as a type of research, research design or research approach. The methodology adopted for this paper is qualitative in nature and involves the analysis of documents and contents. The content of journals and books was analysed to review and draw inferences relating to the themes set out for investigation in the study. Thematic analysis was used for the analysis of data for the study. The study revealed that mixed-methods research was situated within the context of types of research, research design and research approach as evident in the result of the systematic review of the articles selected for the study. Findings from the study further revealed that the conceptualisation of mixed methods within the context type of research and research approach was more than that of a research design. This study is novel and has contributed new knowledge in the aspect of research methodology with specific emphasis and definitive conceptualisation, contextualisation, and categorisation of mixed methods as a type of research, research design or research approach. Just like qualitative and quantitative research, there is a need for definitive conceptualisation, contextualisation, and categorisation of mixed-methods research. Meanwhile, this article is a synthesis for further discourse on mixed-methods research to establish a definitive conclusion on mixed-methods research conceptualisation.